PENATAAN KAWASAN WISATA PANTAI TANJUNG LESTARI DI KABUPATEN SAMBAS - Utari, Erika Tri; Muazir, Syaiful; Mustikawati, Mustikawati (JMARS: Jurnal Mosaik Arsitektur, 2026)
Indonesia, as an archipelagic country, holds great potential in the tourism sector, particularly coastal tourism. Sambas Regency in West Kalimantan, with its natural beauty and scenic beaches, possesses significant potential to be developed into a leading tourist destination. However, several challenges hinder tourism development in the region, such as the lack of facilities, inadequate infrastructure, and insufficient promotion. Although there has been an increase in tourist visits, beach management in Sambas Regency remains unprofessional, and many beaches are equipped with limited amenities. This situation highlights the need to design a more optimized coastal tourism area with complete facilities, including primary, supporting, and complementary infrastructure. The goal of this spatial planning is to create a comfortable, safe, and attractive coastal tourism area by developing facilities that meet the needs of visitors. The design method employed is based on Richard Whitaker's design approach, which comprises the following stages: identification, definition, preparation, analysis, synthesis, evaluation, and re-evaluation. The results of the design process indicate that integrating the components of attraction, amenity, accessibility, and ancillary services can enhance the quality of the area while also supporting the sustainable economic empowerment of the local community.